Military logistic as a tourist resource: on the example of sights of First World War - Смирнов, Ігор (Human Geography Journal, 2014)
Revealed importance of cemeteries of World War I as a tourist resource for the development of "sentimental" tourism on example of Poland, at whose territory in the years 1914-1915 there were two major battles of the Eastern Front – Tannenberg’s and Łódź’s with a total death toll of more than 200 thousand each. Shown significance of military logistics as an important factor in winning these battles. Particularly that conserns the supply, transport, communications and other technical and logistical support to troops that played a key role for the winners in these battles. Among the dead soldiers were not only Germans and Russians but Ukrainian and Polish, as is evident from the inscriptions in cemeteries that are currently recovered through the efforts of the Polish authorities, German and Russian embassies.